2022
DOI: 10.1007/s11160-022-09722-x
|View full text |Cite
|
Sign up to set email alerts
|

Fishers’ knowledge on a large floodplain river in South America. Contributions for sustainable management of inland fisheries

Abstract: This study presents a comparison between fishers’ knowledge and fiscal records about the structure of inland fisheries in the Paraná River (Argentina). First of all, we characterized the fishing population according to the main demographic and economic indicators, identifying two different fishing areas: the northern and southern sections in the lower La Plata basin. Secondly, we carried out a comparative analysis of fiscal fishery records (from two commercial sets: 1930–1984 and 2011–2019) and local fishers’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Accessing fishing information with fishers in the years after the fisheries were carried out can be useful, especially when there is no systematic data collection, as is the case with freshwater fisheries in Brazil. Other studies conducted via interviews with fishers to obtain the amount of fish caught and the composition of the species, which fish are more valued, and how fish abundance and sizes vary over time have shown that this methodology is accurate (Silvano and Hallwass, 2020;Tregidgo et al, 2021;Rabuffetti et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Accessing fishing information with fishers in the years after the fisheries were carried out can be useful, especially when there is no systematic data collection, as is the case with freshwater fisheries in Brazil. Other studies conducted via interviews with fishers to obtain the amount of fish caught and the composition of the species, which fish are more valued, and how fish abundance and sizes vary over time have shown that this methodology is accurate (Silvano and Hallwass, 2020;Tregidgo et al, 2021;Rabuffetti et al, 2022).…”
Section: Discussionmentioning
confidence: 99%